Sleep Hygiene and Psychosocial Outcomes: Sleep Quality as Mediator in Predicting Insomnia, Anxiety, and Depression - Irish Amalia; Asih, Sali Rahadi (Fakultas Psikologi Universitas YARSI, 2023)
This study evaluated the role of sleep quality as mediator between sleep hygiene and psychosocial outcomes, consisting of insomnia, anxiety, and depressive symptoms. Participants of this study included 225 individuals with an average age of 30.22 (SD 8.92), majority were female (75.11%), and residing in metropolitan areas. Measures included SHI, PSQI, ISI, and HSCL-25. Causal mediation analysis using PROCESS Macro Model 4 with 5,000 bootstrapping iterations was employed to analyze the data. The analysis revealed significant relationships and partial mediating effects after controlling for covariates such as age, gender, and weight. Sleep hygiene significantly predicted sleep quality, with sleep quality mediating the relationship between sleep hygiene and psychosocial outcomes. Direct associations were also observed between sleep hygiene and symptoms of insomnia, anxiety, and depression. Therefore, better sleep hygiene was associated with better sleep quality, in the same manner as better sleep quality was associated with less insomnia, anxiety, and depression.